PENGARUH METODE PEMBELAJARAN KONVENSIONAL TERHADAP KECERDASAN NATURLIS SISWA PADA PEMBELAJARAN IPA DI KELAS IV SDN 1 MEKARSARI SAAT PANDEMI COVID-19 - Devita, Rini; Budiyanto, Cepi (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2022)
So a research with a quantitative approach was carried out with an experiment research method with pre-experimental research design in the form of One-Shoot Case Stud Samples were taken using a saturated non-probability sampling technique with a sample size 22 students in class IV SDN 1 Mekarsari. Research instruments in the form of objective test questionnaires and documentation as a complement. After conducting theresearch, the resul of the research in the naturalist intelligence category in class IV SDN 1 Mekarsari were categorize as quite good, this can be seen from the data from the distribution of questionnaires by 53%, whi for conventional learning methods in science learning in class IV SDN 1 included very good, it ca be seen from the data on the results of the distribution of the objective tests of 83.6%. The resul of data analysis resulted in the magnitude of the correlation coefficient or rxy = 0.470. The resul of the t test produce t count = 2.381> t table = 2.073.